The Effect of Family vs. Non-Family CEOs on Product Innovation in Turkish Family Businesses - Saltuk Karayalcin (Administrative Sciences)
Family businesses are a significant part of the global economy, yet defining them and understanding their features remains a topic of debate. Despite the suggestion that family ownership may lead to conservative innovation strategies, recent research indicates that family businesses can embrace strategic risk in innovation. Governance of innovation in family firms is a growing area of interest, with corporate governance influencing R&D and innovation decisions. The role of CEOs in family businesses is critical for innovation strategies, with family CEOs often prioritizing long-term interests. However, research on innovation in Turkish family businesses is lacking, offering an open area for exploration. This article investigates the influence of CEO type (family vs. non-family) on product innovation, innovation management processes, strategic decision-making, risk-taking behaviors, technology adoption, and emotional attachment within Turkish family businesses. A survey methodology was employed, reaching out to Turkish family businesses with a CEO involved in product innovation. The study found that, while family CEOs exhibit a stronger emotional attachment compared to non-family CEOs, there was no significant difference in the perceived influence of CEOs on product innovation. Non-family CEOs were not significantly more likely to implement formal innovation management processes or prioritize long-term strategic goals over short-term profits. Similarly, there was no significant evidence supporting the notion that non-family CEOs are more likely to engage in risk-taking behaviors compared to family CEOs. The study suggests a need for further research using a larger sample and diverse methodologies to deepen understanding of family business dynamics, particularly in the context of innovation.